Managing resources in erratic environments: An analysis of pastoralist systems in Ethiopia, Niger, and Burkina Faso - McCarthy, Nancy; Dutilly-Diane, Celine; Drabo, Boureima; Kamara, Abdul; Vanderlinden, Jean-Paul (International Food Policy Research Institute, 2004)
This study analyzes the links between risk and the kinds of property rights that have evolved to provide the mobility necessary to raise livestock in drought-prone countries--in this case Burkina Faso, Ethiopia, and Niger. The study also evaluates the impact of cooperation on resource management in these environments. The express purpose of this research is to contribute to the current debate on resource management in highly variable environments, focusing on the impact of climate variability on and the role of cooperation in resource management. More specifically, a conceptual framework is developed to analyze the impact of climatic variability and cooperative capacity on land allocation patterns, stock densities, and patterns of herd mobility. Overall, the empirical results suggest that effective policies for sustainable land management and crisis-response plans may require the design and implementation of mechanisms to increase cooperative capacity.